Governança corporativa e políticas públicas : uma análise da reforma à lei 6.404/76 sob a ótica da proteção aos acionistas minoritários - Santos, Eduardo José dos (2006)
This work is characterized as a field research, whose main goal is the evaluation to the reform of the Law 6.404/76 related to the protection of the policy shareholders. As an instrument of data collection, a field research questionnaire has been used, and its final evaluation will be fundamental with the application of the following statistical methods: 1) Qui-Square (X2) Test, employed to evaluate if there has been an unanimity in the responses to the questionnaire given, seeking to study if there is a concordance profile in the answers; Krustal-Wallis Test (H), which aims to verify if the nil hypothesis of management in the questions applied to the ordinary and preferential participants, in the total of emissions, and the group which controls the companies; and 3) Spearman Correlation Coefficient (rs), that seeks to study if there is a correlation of concordance of the respondents on some of the questions asked, and to the blocks of questions. In general, one identifies the existence of a pattern of concordance of the respondents in that they accept the statements of the questionnaire. It is evident that the Law 10.303/2001, who reforms the Law 6.404/76, still lacks many aspects related to the protection of the policy shareholders, mainly in those based on the emission of preferential shares, in the right of 80% tag along to the investors of the ordinary shares in the case of application or the control block, and the entailing to the will of the shareholders who elected them.